Circulating Expression Level of LncRNA Malat1 in Diabetic Kidney Disease Patients and Its Clinical Significance. (3rd August 2020) - Zhou, Lian-ji; Yang, Da-wei; Ou, Li-Na; Guo, Xing-Rong; Wu, Biao-liang
Abstract : Background. Long noncoding RNA MALAT1 is closely related to diabetes and kidney diseases and is expected to be a new target for the diagnosis and treatment of diabetic nephropathy. Objective. This study aimed to explore the circulating expression level and significance of lncRNA Malat1 in patients with type 2 diabetes mellitus (T2DM) and diabetic kidney disease (DKD). Methods. Quantitative real-time PCR (qPCR) was conducted to assess the expression of lncRNA Malat1 in 20 T2DM patients, 27 DKD patients, and 14 healthy controls, and then, the clinical significance was analyzed. Results. LncRNA MALAT1 expression in peripheral blood mononuclear cells (PBMC) was significantly upregulated in T2DM and DKD groups when compared to control. Pearson's correlation analysis showed correlation of lncRNA MALAT1 levels with ACR, urine β 2-microglobulin ( β 2-MG), urine α 1-microglobulin ( α 1-MG), creatinine (Cr), and glycosylated hemoglobin (HbA1c), while negative with superoxide dismutase (SOD) (r = − 0.388, P < 0.05 ). Binary regression analysis showed that ACR, creatinine, α 1-MG, and LncRNA Malat1 were the risk factors for diabetic nephropathy with OR value of 1.166, 1.031, 1.031, and 2.019 (P < 0.05 ). The area under ROC curve (AUC) of DKD identified by the above indicators was 0.914, 0.643, 0.807, and 0.797, respectively. The AUC of Joint prediction probability of DKD recognition was 0.914, and the sensitivity and specificity of DKD diagnosis were 1.0 and 0.806, respectively. (Take ≥0.251 as the diagnostic cutoff point). Conclusion. LncRNA Malat1 is highly expressed in DKD patients, and the combined detection of ACR, creatinine, α 1-MG, and LncRNA Malat1 with diabetes mellitus may be the best way to diagnose diabetic nephropathy.